De enfermeira a parteira: uma análise etnográfica da Equipe Manjedoura no município de Cascavel (PR) - Fagundes, Ana Paula Soares (2018)
The midwife as a profession has undergone great transformations during the last centuries, turning from a body of knowledge built on practice to a regulated profession, through specific training in the area of Obstetric Nursing or Obstetrics, what ultimately lead to the emergence of the so-called “urban midwives”. With the medicalization of childbirth, the change from domestic to hospital environment, the parturient and the fetus have lost their protagonist roles at birth - as reported by advocates of humanized childbirth - and various professionals started to have control over a series of interventions. Currently there are attempts to rescue traditional practices and the possibility of the delivery to be performed with elements considered to be natural, in a family environment and with reduced intervention. In this scenario, the role of the "urban midwife" reappears, adding to other subjects, such as doulas, in practices that contrast or combine traditional and medical knowledge. This research aims to anthropologically analyze the practices of the "urban midwives" in the municipality of Cascavel / PR, seeking to understand the construction of the midwife as a subject, in a contemporaneity marked by the scientific aspect of medical practices. In order to achieve this goal, the research is divided in three chapters: in the first one, I introduce the trajectory of the midwives who work in a team focused on humanized childbirth; following it, I analyze the team’s background and their action in the virtual space; and, finally, the midwife practices are analyzed within the observation of three home births in the city of Cascavel / PR. Some aspects are highlighted in the accomplishment of the research, such as: the matter of religiosity, which underlines the performance of the "urban midwives"; the virtual interaction of the team with its clientele; the notions of body, family and relations of power, which intersect in the context of birth.